Hot-pack therapy increased gliding function of the iliotibial band during passive knee motion: An exploratory study. - Ishida, Hiroshi; Suehiro, Tadanobu; Oku, Kosuke; Yoshimura, Yosuke (Journal of Bodywork & Movement Therapies, 2024)
Quantifying soft tissue dynamics during joint motion is important for the valid assessment and development of effective therapeutic interventions for the soft tissues. This study aimed to examine the immediate effect of thermotherapy on gliding of the iliotibial band (ITB), including the subcutaneous tissue, and vastus lateralis (VL) muscle during passive knee joint motion. Ten participants (age, 20.4 ± 0.7 years; height, 172.0 ± 8.9 cm; weight, 64.1 ± 9.7 kg; BMI, 21.6 ± 1.7 kg/m2) with no history of lower extremity surgery or neuromuscular disease participated in the study. An electrothermal hot pack with an internal temperature of 65 °C was applied to one of the lateral thighs, followed by measuring its stiffness using a durometer. Movements of both the ITB and VL were recorded using ultrasound imaging during isokinetic knee motion. The Farneback method and optical flow algorithm analysis software were adapted to create the movement velocity from ultrasound imaging. Gliding coefficient was calculated using the coefficient of correlation for each velocity in the proximal-distal direction during knee motion. The mean velocity during knee motion was calculated using absolute values. The differences between the pre-intervention values and between the pre- and post-intervention values were examined. After applying the hot pack, the stiffness significantly decreased (p = 0.01), and the mean velocity of the ITB significantly increased (p = 0.03). The gliding coefficient and VL mean velocity did not significant differ (p = 0.65 and p = 0.80, respectively) between pre- and post-hot-pack applications. Hot-pack therapy might increase gliding function of the ITB during passive knee motion. • Thermotherapy decreased the soft tissue stiffness of the lateral thigh. • Thermotherapy increased the ITB gliding function during passive knee motion. • Thermotherapy did not alter the gliding function of the VL.